Nitrogen-doped carbon electrode material, preparation method thereof and flow battery
By using nitrogen-doped carbon electrode materials in all vanadium flow batteries, adjusting the electronic structure of the carbon skeleton and designing gradient porosity and flow field structure, the problem of low efficiency of existing electrode materials is solved and higher battery performance is achieved and longer stack life.
Patent Information
- Application Number
- CN202411634978.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-01-10
AI Technical Summary
The electrode materials of existing all-vanadium flow batteries lead to low voltage and energy efficiency, and improvements are urgently needed to improve the battery performance.
Using nitrogen-doped carbon electrode material, by introducing nitrogen atoms into the carbon framework, adjusting the electronic structure, increasing the active site, and designing gradient porosity and flow field structures in multiple dimensions to ensure uniform distribution of the electrolyte and reducing concentration difference. polarization.
It improves the overall performance of the flow battery, improves voltage efficiency and energy efficiency, extends the life of the stack, and avoids the impurity problems caused by the addition of zinc chloride.
Smart Images

Figure CN119284896A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of liquid flow batteries, and in particular relates to a nitrogen-doped carbon electrode material, a preparation method thereof and a liquid flow battery. Background Art
[0002] All-vanadium liquid flow battery (VRFB) energy storage occupies an important position in energy storage systems with its superior cycle life and good safety. It is widely used in large-scale energy storage solutions in power systems, especially in supporting the integration of renewable energy and grid stability.
[0003] In order to further improve the performance of the battery stack, the design of electrode materials still needs to be improved and optimized. Currently, porous carbon materials are usually used as electrodes for all-vanadium liquid flow batteries, such as carbon felt and carbon cloth. However, the voltage efficiency and energy efficiency of liquid flow batteries made of existing materials are low.
[0004] Therefore, there is an urgent need to develop an electrode material that can improve the voltage efficiency and energy efficiency of flow batteries. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the present invention proposes a method for preparing a nitrogen-doped carbon electrode material. During the preparation process, nitrogen atoms are directly introduced into the carbon skeleton to adjust the electronic structure of the carbon material, increase active sites, and accelerate the ion redox reaction, thereby improving the overall performance of the battery; further, the nitrogen-doped carbon electrode material can be a gradient nitrogen-doped carbon electrode material, and the gradient nitrogen-doped carbon electrode material can be designed with gradient porosity in multiple dimensions, so that the porosity of the nitrogen-doped carbon electrode material gradually increases from the direction of the electrolyte inlet to the liquid outlet, and from the current collecting plate side to the ion membrane side; at the same time, the nitrogen-doped carbon electrode material can have a flow field structural design; the gradient porosity and flow field structural designs are both conducive to the uniform distribution of the electrolyte in the electrode, reducing concentration polarization, and improving the overall efficiency of the battery stack.
[0006] The present invention provides a method for preparing a nitrogen-doped carbon electrode material, the method comprising the following steps:
[0007] (1) dissolving an amine-containing hydrophilic polymer in water to obtain a first hydrogel precursor solution; dissolving an aldehyde-containing hydrophilic polymer in water to obtain a second hydrogel precursor solution; mixing the first hydrogel precursor solution and the second hydrogel precursor solution evenly, pouring the mixture into a mold, sealing the mold and allowing the mold to stand to obtain a solidified hydrogel;
[0008] (2) pre-freezing the solidified hydrogel and then freeze-drying it to obtain a freeze-dried hydrogel with a self-supporting structure;
[0009] (3) The freeze-dried hydrogel is carbonized and activated to obtain a nitrogen-doped carbon electrode material.
[0010] In one or more embodiments, in step (1), the amino-containing hydrophilic polymer is selected from one or more of chitosan, carboxymethyl chitosan, polyethyleneimine and gelatin.
[0011] In one or more embodiments, in step (1), the concentration of the amino-containing hydrophilic polymer in the first hydrogel precursor solution is 0.5 to 2 mol / L.
[0012] In one or more embodiments, in step (1), the aldehyde-containing hydrophilic polymer is selected from one or more of oxidized alginate, oxidized hyaluronic acid and polyacrylaldehyde.
[0013] In one or more embodiments, in step (1), the concentration of the aldehyde-containing hydrophilic polymer in the second hydrogel precursor solution is 0.5 to 2 mol / L.
[0014] In one or more embodiments, in step (1), the first hydrogel precursor solution and the second hydrogel precursor solution are mixed in a volume ratio of (1-3):1.
[0015] In one or more embodiments, in step (1), the mold is a common mold with a flat and smooth bottom or a flow field mold with a convex or concave structure on the bottom.
[0016] In one or more embodiments, in step (1), the standing time is 0.5 to 6 hours.
[0017] In one or more embodiments, in step (2), the pre-freezing temperature is -15 to -5°C.
[0018] In one or more embodiments, in step (2), the pre-freezing time is 8 to 24 hours.
[0019] In one or more embodiments, in step (2), the freeze-drying temperature is -50 to -40°C.
[0020] In one or more embodiments, in step (2), the vacuum degree of freeze drying is 10-20 Pa.
[0021] In one or more embodiments, in step (2), the freeze-drying time is 24 to 72 hours.
[0022] In one or more embodiments, in step (3), the temperature of the carbonization treatment is 600-700°C.
[0023] In one or more embodiments, in step (3), the heating rate of the carbonization treatment is 10 to 50° C. / min.
[0024] In one or more embodiments, in step (3), the heat preservation time of the carbonization treatment is 2 to 5 hours.
[0025] In one or more embodiments, in step (3), carbonization is performed in an inert gas or nitrogen atmosphere.
[0026] In one or more embodiments, in step (3), steam activation or air activation is used.
[0027] In one or more embodiments, in step (3), the temperature of the activation treatment is 300-600°C.
[0028] In one or more embodiments, in step (3), the heating rate of the activation treatment is 10 to 50° C. / min.
[0029] In one or more embodiments, in step (3), the activation treatment is carried out for a holding time of 2 to 5 hours.
[0030] In one or more embodiments, the method further comprises step (1'): preparing solidified hydrogels of different concentrations according to the operation of step (1), cutting the solidified hydrogels of different concentrations to obtain solidified hydrogel strips of different concentrations, fitting the solidified hydrogel strips of different concentrations along the cut surface, placing them in a mold, sealing and standing them to obtain reconstituted solidified hydrogels, and then performing the operations of steps (2) and (3) on the reconstituted solidified hydrogels.
[0031] In one or more embodiments, in step (1'), the cutting method is horizontal cutting or vertical cutting.
[0032] In one or more embodiments, in step (1'), the bonded solidified hydrogel strip is placed in the mold in a manner that the cut surface is parallel or perpendicular to the bottom of the mold.
[0033] In one or more embodiments, in step (1'), the mold is a common mold with a flat and smooth bottom or a flow field mold with a convex or concave structure on the bottom.
[0034] In one or more embodiments, in step (1'), the standing time is 3 to 6 hours.
[0035] In one or more embodiments, the molds used in step (1) and step (1') are the same or different.
[0036] The present invention provides a nitrogen-doped carbon electrode material prepared by the method of the present invention, wherein the nitrogen-doped carbon electrode material is a single-layer nitrogen-doped carbon electrode material or a gradient nitrogen-doped carbon electrode material.
[0037] In one or more embodiments, the nitrogen-doped carbon electrode material has a flow field.
[0038] In one or more embodiments, the porosity of the gradient nitrogen-doped carbon electrode material changes in a gradient.
[0039] In one or more embodiments, the gradient number of the gradient nitrogen-doped carbon electrode material is ≥1.
[0040] In one or more embodiments, the gradient nitrogen-doped carbon electrode material includes a thickness gradient nitrogen-doped carbon electrode material or a vertical gradient nitrogen-doped carbon electrode material.
[0041] In one or more embodiments, the porosity of the thickness gradient nitrogen-doped carbon electrode material changes gradiently in the thickness direction.
[0042] In one or more embodiments, the porosity of the vertically gradient nitrogen-doped carbon electrode material varies in a gradient in a direction perpendicular to the thickness.
[0043] The present invention provides a liquid flow battery comprising the nitrogen-doped carbon electrode material of the present invention.
[0044] Compared with the prior art, the present invention has the following beneficial effects:
[0045] (1) The present invention directly introduces nitrogen atoms into the carbon skeleton during the preparation process, which adjusts the electronic structure of the carbon material, increases the active sites, and accelerates the ion redox reaction, thereby improving the overall performance of the flow battery;
[0046] (2) In the present invention, two types of cured hydrogels form a three-dimensional cross-linked network hydrogel through dynamic Schiff base bonds. This Schiff base bonding method has a certain reversibility. After cutting this self-healing hydrogel, the cured hydrogel blocks of different concentrations are attached along the cut surface and left to stand, the veneered cured hydrogels are cross-linked and self-healed through the Schiff base bonds. Therefore, the porosity in the cut surface direction is not much different from that of the two cut surfaces, and there will be no porosity fault; this is conducive to designing flow fields and gradient porosity in nitrogen-doped carbon electrode materials;
[0047] (3) The present invention designs the gradient porosity of the nitrogen-doped carbon electrode material in multiple dimensional directions, so that the porosity of the nitrogen-doped carbon electrode material gradually increases from the electrolyte inlet to the electrolyte outlet and from the current collecting plate side to the ion membrane side, thereby making the electrolyte evenly distributed in the electrode material, reducing concentration polarization, and improving the overall efficiency of the liquid flow battery;
[0048] (4) The present invention designs a flow field structure in the nitrogen-doped carbon electrode material. The design of the flow field structure is conducive to better penetration of the electrolyte into the electrode material, reducing the pressure drop, and improving the mass transfer, thereby improving the stability of the flow battery and extending the life of the battery stack;
[0049] (5) The present invention does not require the addition of zinc chloride. The addition of zinc chloride may assist in dissolution or increase the mechanical strength of the gel, but zinc chloride will be converted into zinc oxide during the subsequent calcination process and become an impurity of the electrode material, which has an adverse effect on the electrode performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 This is a schematic diagram of the structure of the thickness gradient nitrogen-doped carbon electrode material prepared in Example 6 of the present invention.
[0051] Figure 2 Schematic diagram of the structure of the flow field mold according to some embodiments of the present invention.
[0052] Figure 3 A reference diagram for electrode cutting methods in some embodiments of the present invention.
[0053] Figure 4 This is a scanning electron microscope image of the freeze-dried hydrogel prepared in Example 1 of the present invention.
[0054] Figure 5 Schematic diagram of the porosity testing method of the test example of the present invention. DETAILED DESCRIPTION
[0055] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0056] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0057] Herein, “comprising”, “including”, “containing” and similar terms encompass the meanings of “consisting essentially of” and “consisting of”. For example, when “A comprises B and C” is disclosed herein, “A consists essentially of B and C” and “A consists of B and C” should be deemed to be disclosed herein.
[0058] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are only for brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0059] In this document, unless otherwise specified, percentage refers to mass percentage and ratio refers to mass ratio.
[0060] Herein, when describing embodiments or examples, it should be understood that they are not used to limit the present invention to these embodiments or examples. On the contrary, all substitutes, improvements and equivalents of the methods and materials described in the present invention can be included in the scope limited by the claims.
[0061] In this article, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification. The present invention provides a method for preparing a nitrogen-doped carbon electrode material, the method comprising the following steps:
[0062] (1) dissolving an amine-containing hydrophilic polymer in water to obtain a first hydrogel precursor solution, dissolving an aldehyde-containing hydrophilic polymer in water to obtain a second hydrogel precursor solution, mixing the first hydrogel precursor solution and the second hydrogel precursor solution evenly, pouring the mixture into a mold, sealing the mold and allowing the mold to stand to obtain a solidified hydrogel;
[0063] (2) pre-freezing the solidified hydrogel and then freeze-drying it to obtain a freeze-dried hydrogel with a self-supporting structure;
[0064] (3) The freeze-dried hydrogel is carbonized and activated to obtain a nitrogen-doped carbon electrode material.
[0065] In step (1), the hydrophilic polymer containing an amine group may be one or more selected from chitosan, carboxymethyl chitosan, polyethyleneimine and gelatin. The present invention uses the hydrophilic polymer containing an amine group as a precursor material for synthesizing a solidified hydrogel, which is conducive to directly preparing a nitrogen-doped electrode material, and the introduction of the nitrogen element improves the electrochemical activity of the electrode and promotes the redox reaction of ions. In some embodiments, the nitrogen-doped carbon electrode material prepared from the hydrophilic polymer containing an amine group is used in an all-vanadium liquid flow battery, which is conducive to improving the electrochemical activity of the electrode material, promoting the redox reaction of vanadium ions, and thereby improving the voltage efficiency and energy efficiency of the liquid flow battery.
[0066] In step (1), the concentration of the amino-containing hydrophilic polymer in the first hydrogel precursor solution may be 0.5 to 2 mol / L, for example, 0.5 mol / L, 1 mol / L, 1.5 mol / L, or 2 mol / L.
[0067] In step (1), the hydrophilic polymer containing aldehyde groups can be one or more selected from oxidized alginate, oxidized hyaluronic acid and polyacrylaldehyde. In the present invention, the hydrophilic material is the prerequisite for synthesizing the hydrogel. The hydrophilic materials of the aldehyde group and the amine group can form a hydrogel through an amide bond, which is beneficial for directly preparing the electrode material doped with nitrogen, improving the electrochemical activity of the electrode, promoting the redox reaction of the ions, and thus improving the voltage efficiency and energy efficiency of the flow battery.
[0068] In step (1), the oxidized alginate may be oxidized sodium alginate and / or oxidized potassium alginate.
[0069] In step (1), the concentration of the aldehyde-containing hydrophilic polymer in the second hydrogel precursor solution may be 0.5 to 2 mol / L, for example, 0.5 mol / L, 1 mol / L, 1.5 mol / L, or 2 mol / L.
[0070] In the present invention, a hydrophilic polymer containing an amine group is dissolved in water, heated and shaken to obtain a first hydrogel precursor solution, and a hydrophilic polymer containing an aldehyde group is dissolved in water, heated and shaken to obtain a second hydrogel precursor solution. The present invention uses heating and shaking to promote the dissolution of raw materials in water.
[0071] In step (1), the first hydrogel precursor solution and the second hydrogel precursor solution may be mixed in a volume ratio of (1-3):1, for example, 1:1, 1.5:1, 2:1, 2.5:1, 3:1.
[0072] In step (1), the mold can be a common mold with a smooth bottom or a flow field mold with a convex or concave structure on the bottom. Figure 2 The solidified hydrogel with flow field is synthesized as shown in the figure, thereby preparing nitrogen-doped carbon electrode material with flow field. The design of flow field enables the electrolyte to better penetrate into the electrode material, reduce pressure drop, and improve mass transfer, thereby improving the stability of the battery stack and extending the life of the battery stack.
[0073] In step (1), the standing time can be 0.5 to 6 h, for example, 0.5 h, 1.0 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, 5 h, 5.5 h, and 6 h.
[0074] In the present invention, after freeze-drying, the solidified hydrogel is freed of water and retains a cross-linked structure, so that the freeze-dried hydrogel has a certain stiffness, and thus the freeze-dried hydrogel has a self-supporting structure.
[0075] In step (2), the pre-freezing temperature can be -15 to -5°C, for example, -5°C, -7°C, -9°C, -11°C, -13°C, -15°C. In step (2), the pre-freezing time can be 8 to 24h, for example, 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h, 24h.
[0076] In step (2), the freeze drying temperature can be -50 to -40°C, for example, -50°C, -48°C, -46°C, -44°C, -42°C, -40°C. In step (2), the vacuum degree of freeze drying can be 10 to 20 Pa, for example, 10 Pa, 12 Pa, 14 Pa, 16 Pa, 18 Pa, 20 Pa. In step (2), the freeze drying time can be 24 to 72 h, for example, 24 h, 28 h, 32 h, 36 h, 40 h, 44 h, 48 h, 52 h, 56 h, 60 h, 64 h, 68 h, 72 h.
[0077] In step (3), the temperature of the carbonization treatment can be 600-700°C, for example, 600°C, 620°C, 640°C, 660°C, 680°C, 700°C. In step (3), the heating rate of the carbonization treatment can be 10-50°C / min, for example, 10°C / min, 15°C / min, 20°C / min, 25°C / min, 30°C / min, 35°C / min, 40°C / min, 45°C / min, 50°C / min. In step (3), the holding time of the carbonization treatment can be 2-5h, for example, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h.
[0078] In step (3), carbonization can be carried out in an inert gas or nitrogen atmosphere. In the present invention, the inert gas can be one or more selected from argon, helium and neon.
[0079] In step (3), water vapor activation or air activation can be used. In step (3), the temperature of the activation treatment can be 300-600°C, for example, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C. In step (3), the heating rate of the activation treatment can be 10-50°C / min, for example, 10°C / min, 15°C / min, 20°C / min, 25°C / min, 30°C / min, 35°C / min, 40°C / min, 45°C / min, 50°C / min. In step (3), the holding time of the activation treatment can be 2-5h, for example, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h.
[0080] The method for preparing nitrogen-doped carbon electrode material of the present invention also includes step (1'): preparing cured hydrogels of different concentrations according to the operation of step (1), cutting the cured hydrogels of different concentrations to obtain cured hydrogel strips of different concentrations, laminating the cured hydrogel strips of different concentrations along the cut surface, placing them in a mold and sealing them to stand, obtaining a reconstituted cured hydrogel, and then performing the operations of step (2) and step (3) on the reconstituted cured hydrogel. In the present invention, a three-dimensional cross-linked network hydrogel is formed between the two cured hydrogels through a dynamic Schiff base bond, and this Schiff base bonding method has a certain reversibility, so the self-healing hydrogel is cut, and the cured hydrogel blocks of different concentrations are laminating along the cut surface direction and standing for a period of time, and the veneered cured hydrogel is cross-linked and self-healed by the Schiff base bond, so the porosity in the cut surface direction is not much different from that of the two cut surfaces, and there will be no porosity fault. Therefore, the material can be used to simply realize the preparation of electrode materials with flow fields and the preparation of electrode materials with multi-gradient porosity, and the number of porosity gradients and the arrangement of gradients can be arbitrarily adjusted according to the applicable situation and needs.
[0081] In the present invention, the porosity of the nitrogen-doped carbon electrode material prepared by the low-concentration cured hydrogel is greater than that of the nitrogen-doped carbon electrode material prepared by the high-concentration cured hydrogel. This is because the low-concentration cured hydrogel has a high water content and a larger pore size of the cross-linked network.
[0082] In step (1'), the cutting method can be horizontal cutting or vertical cutting.
[0083] In step (1'), the bonded solidified hydrogel strip can be placed in the mold in a manner that the cut surface is parallel or perpendicular to the bottom of the mold.
[0084] In step (1'), the mold can be a common mold with a flat and smooth bottom or a flow field mold with a convex or concave structure on the bottom. In some embodiments, a solidified hydrogel with a flow field can be synthesized by a flow field mold to prepare a nitrogen-doped carbon electrode material with a flow field. The design of the flow field allows the electrolyte to better penetrate into the electrode material, reduce the pressure drop, and improve the mass transfer, thereby improving the stability of the battery stack and extending the life of the battery stack.
[0085] In the present invention, the flow field mold may have a flow channel, and the dimensions of the flow channel may be: 45 mm to 52 mm in length, 0.8 mm to 1.2 mm in width, and 0.5 to 1.2 mm in height. In some embodiments, the length, width, and height of the flow channel are 52 mm, 1.2 mm, and 1 mm, respectively.
[0086] In step (1'), the standing time can be 3 to 6 hours, for example, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, and 6 hours.
[0087] In the present invention, the molds used in step (1) and step (1') may be the same or different.
[0088] The present invention provides a nitrogen-doped carbon electrode material prepared by the preparation method of the present invention. The nitrogen-doped carbon electrode material of the present invention adjusts the electronic structure of the carbon material, increases active sites, accelerates ion redox reactions, and thus improves the overall performance of the battery by directly introducing nitrogen atoms into the carbon skeleton.
[0089] In the present invention, the nitrogen-doped carbon electrode material may be a single-layer nitrogen-doped carbon electrode material or a gradient nitrogen-doped carbon electrode material.
[0090] In the present invention, the porosity of the gradient nitrogen-doped carbon electrode material may vary in a gradient.
[0091] In the present invention, the gradient of the gradient nitrogen-doped carbon electrode material is ≥1, preferably 2-5, for example 3, 4. In the present invention, the gradient of n means that the nitrogen-doped carbon electrode material has an n+1 layer structure with different porosities. In the present invention, the two cured hydrogels form a three-dimensional cross-linked network hydrogel through a dynamic Schiff base bond. This Schiff base bonding method has a certain reversibility. Therefore, the self-healing hydrogel is cut, and the cured hydrogel blocks of different concentrations are attached along the cut surface direction and left to stand for a period of time. The veneered cured hydrogel is cross-linked and self-healed by the Schiff base bond. Therefore, the porosity in the cut surface direction is not much different from that of the two cut surfaces, and there will be no porosity fault. Therefore, the material can be used to simply realize the preparation of multi-gradient porosity electrode materials, and the number of porosity gradients and the arrangement of the gradients can be arbitrarily adjusted according to the applicable situation and needs. In some embodiments, the gradient of the gradient nitrogen-doped carbon electrode material is 2, and the gradient nitrogen-doped carbon electrode material at this time has three pores of different sizes along a specific direction.
[0092] In the present invention, the gradient nitrogen-doped carbon electrode material includes a thickness gradient nitrogen-doped carbon electrode material and a vertical gradient nitrogen-doped carbon electrode material. In the present invention, considering the structural characteristics of the flow battery, the electrolyte reacts fastest on the side of the electrode close to the current collecting plate, and the electrolyte is easily deposited at the liquid inlet, so the nitrogen-doped carbon electrode material is subjected to multi-gradient porosity structure design and / or flow field structure design to obtain a gradient nitrogen-doped carbon electrode material and / or a nitrogen-doped carbon electrode material with a flow field. This structural design is conducive to the uniform distribution of the electrolyte in the electrode, reducing concentration polarization, and improving the overall efficiency of the battery stack.
[0093] In the present invention, the porosity of the thickness gradient nitrogen-doped carbon electrode material can change in a gradient in the thickness direction. When the thickness gradient nitrogen-doped carbon electrode material prepared by the present invention is assembled into a flow battery, the porosity from the current collector side to the ion membrane side gradually decreases, which is conducive to the uniform distribution of the electrolyte in the electrode material, reduces concentration polarization, and improves the overall efficiency of the battery stack.
[0094] In the present invention, the porosity of the vertical gradient nitrogen-doped carbon electrode material can change in a gradient in the direction perpendicular to the thickness. When the vertical gradient nitrogen-doped carbon electrode material prepared by the present invention is assembled into a flow battery, the porosity in the direction from the electrolyte inlet to the electrolyte outlet gradually decreases, which is conducive to the uniform distribution of the electrolyte in the electrode material, reduces concentration polarization, and improves the overall efficiency of the battery stack.
[0095] In the present invention, the nitrogen-doped carbon electrode material may have a flow field. In the present invention, considering the structural characteristics of the flow battery, the electrolyte reacts fastest on the side of the electrode close to the current collecting plate, and the electrolyte is easily deposited at the liquid inlet, so the nitrogen-doped carbon electrode material is designed with a flow field to obtain a nitrogen-doped carbon electrode with a flow field. The nitrogen-doped carbon electrode material with a flow field prepared by the present invention, the design of this flow field is conducive to better penetration of the electrolyte into the electrode material, reducing the pressure drop, and improving the mass transfer, thereby improving the stability of the battery stack and extending the life of the battery stack.
[0096] In the present invention, the nitrogen-doped carbon electrode material can have both a gradient structural design and a flow field structural design, which synergistically promotes better penetration of the electrolyte into the electrode material, thereby improving the voltage efficiency and energy efficiency of the flow battery. In some embodiments, the vertical gradient nitrogen-doped carbon electrode material has a flow field, specifically Figure 1 As shown, the vertical gradient nitrogen-doped carbon electrode material is located between the current collector and the ion membrane, and the vertical gradient nitrogen-doped carbon material is divided into three layers, which are the first gradient, the second gradient and the third gradient from the current collector side to the ion membrane side, and the concentration is low and the porosity is high near the current collector side; further, the first gradient near the current collector side is the flow channel side, which has a flow field, and the small squares therein are the flow channels from the first perspective; Figure 1 The structural design of the mid-flow channel and gradient both facilitate the passage of electrolyte, which is beneficial to improving the voltage efficiency and energy efficiency of the flow battery.
[0097] The present invention provides a liquid flow battery comprising the nitrogen-doped carbon electrode material of the present invention.
[0098] The present invention will be described below in the form of specific examples. It should be understood that these examples are merely illustrative and are not intended to limit the scope of the present invention. The methods, reagents and materials used in the examples are, unless otherwise stated, conventional methods, reagents and materials in the art. The raw material compounds in the examples can all be purchased through commercial routes.
[0099] The gelatin in the examples and comparative examples of the present invention was purchased from Aladdin.
[0100] The oxidized sodium alginate in the examples and comparative examples of the present invention was purchased from Xi'an Qiyue Biotechnology Co., Ltd.
[0101] Example 1
[0102] In this embodiment, a single-layer nitrogen-doped carbon electrode material is prepared, and the specific steps are as follows:
[0103] 1. Dissolve 0.5 mol of gelatin in 500 mL of deionized water, heat and shake to obtain a first hydrogel precursor solution; dissolve 0.5 mol of oxidized sodium alginate in 500 mL of deionized water, heat and shake to obtain a second hydrogel precursor solution; mix 300 mL of the first hydrogel precursor solution and 300 mL of the second hydrogel precursor solution, pour into a common mold with a flat and smooth bottom of 10 cm in length, 10 cm in width and 10 cm in height, seal it, and let it stand for 5 hours to obtain a solidified hydrogel;
[0104] 2. The solidified hydrogel was placed in a refrigerator at -15°C for 12 hours and then freeze-dried in a freeze dryer; wherein the cold trap temperature of the freeze dryer was -40°C, the vacuum degree was 20Pa, and the freeze drying time was 48 hours to obtain a freeze-dried hydrogel with a self-supporting structure (such as Figure 4 shown);
[0105] 3. The freeze-dried hydrogel was carbonized at 600°C for 4 h, with a carbonization heating rate of 30°C / min and an argon atmosphere, and then treated with water vapor activation for 3 h, with an activation temperature of 500°C and an activation heating rate of 30°C / min, to obtain a single-layer nitrogen-doped carbon electrode material.
[0106] Example 2
[0107] The other conditions of this example are the same as those of Example 1, except that the amount of gelatin used in this example is 0.7 mol, and the amount of oxidized sodium alginate used is 0.7 mol.
[0108] Example 3
[0109] In this embodiment, a thickness gradient nitrogen-doped carbon electrode material is prepared, and the specific steps are as follows:
[0110] 1. Dissolve 0.5 mol of gelatin in 500 mL of deionized water, heat and shake to obtain a first hydrogel precursor solution; dissolve 0.5 mol of oxidized sodium alginate in 500 mL of deionized water, heat and shake to obtain a second hydrogel precursor solution; mix 300 mL of the first hydrogel precursor solution and 300 mL of the second hydrogel precursor solution, pour into a common mold with a flat and smooth bottom of 10 cm, 10 cm, and 10 cm in length, width, and height, respectively, and seal it, let it stand for 1 hour, and obtain a cured hydrogel 1;
[0111] 2. The amount of gelatin and oxidized sodium alginate in step (1) is adjusted to 0.3 mol, and the operation of step (1) is repeated to obtain solidified hydrogel 2; the amount of gelatin and oxidized sodium alginate in step (1) is adjusted to 0.7 mol, and the operation of step (1) is repeated to obtain solidified hydrogel 3; solidified hydrogel 1, solidified hydrogel 2 and solidified hydrogel 3 are respectively cut horizontally into three solidified hydrogel strips with a length, width and height of 10 cm×10 cm×2 cm; the three solidified hydrogel strips are transferred to a common mold with a smooth bottom with a length, width and height of 10 cm, 10 cm and 6 cm, respectively, in a gradual order of concentration gradient, without leaving any gaps, and sealed, and allowed to stand for 4 hours to obtain a reconstituted solidified hydrogel (when assembling the battery, the low concentration side is close to the collector side, and the high concentration side is close to the ion membrane side);
[0112] 3. Pre-freeze the reconstituted solidified hydrogel in a refrigerator at -15°C for 12 hours, and then freeze-dry it in a freeze dryer; wherein the cold trap temperature of the freeze dryer is -40°C, the vacuum degree is 20Pa, and the freeze drying time is 48 hours to obtain a freeze-dried hydrogel with a self-supporting structure;
[0113] 4. The freeze-dried hydrogel was carbonized at 600°C for 4 h, with a carbonization heating rate of 30°C / min and an argon atmosphere, and then treated with water vapor activation for 3 h, with an activation temperature of 500°C and an activation heating rate of 30°C / min to obtain a thickness gradient nitrogen-doped carbon electrode material.
[0114] Example 4
[0115] In this embodiment, vertical gradient nitrogen-doped carbon electrode materials are prepared, and the specific steps are as follows:
[0116] 1. Dissolve 0.5 mol of gelatin in 500 mL of deionized water, heat and shake to obtain a first hydrogel precursor solution; dissolve 0.5 mol of oxidized sodium alginate in 500 mL of deionized water, heat and shake to obtain a second hydrogel precursor solution; mix 300 mL of the first hydrogel precursor solution and 300 mL of the second hydrogel precursor solution, pour into a common mold with a flat and smooth bottom of 10 cm, 10 cm, and 10 cm in length, width, and height, respectively, and seal it, let it stand for 1 hour, and obtain a cured hydrogel 1;
[0117] 2. The amount of gelatin and oxidized sodium alginate in step (1) is adjusted to 0.3 mol, and the operation of step (1) is repeated to obtain solidified hydrogel 2; the amount of gelatin and oxidized sodium alginate in step (1) is adjusted to 0.7 mol, and the operation of step (1) is repeated to obtain solidified hydrogel 3; solidified hydrogel 1, solidified hydrogel 2 and solidified hydrogel 3 are cut into three solidified hydrogel strips with a length, width and height of 3.33 cm × 10 cm × 6 cm respectively along the width and height directions; the three solidified hydrogel strips are transferred to a common mold with a smooth bottom with a length, width and height of 10 cm, 10 cm and 6 cm respectively in a gradual order of concentration gradient, and sealed, and left to stand for 4 hours to obtain a reconstituted solidified hydrogel (when assembling the battery, the surface with low concentration is close to the liquid inlet, and the surface with high concentration is close to the liquid outlet);
[0118] 3. Pre-freeze the reconstituted solidified hydrogel in a refrigerator at -15°C for 12 hours, and then freeze-dry it in a freeze dryer; wherein the cold trap temperature of the freeze dryer is -40°C, the vacuum degree is 20Pa, and the freeze drying time is 48 hours to obtain a freeze-dried hydrogel with a self-supporting structure;
[0119] 4. The freeze-dried hydrogel was carbonized at 600°C for 4 h, with a carbonization heating rate of 30°C / min and an argon atmosphere, and then treated with water vapor activation for 3 h, with an activation temperature of 500°C and an activation heating rate of 30°C / min to obtain a vertical gradient nitrogen-doped carbon electrode material.
[0120] Example 5
[0121] The other conditions of this embodiment are the same as those of embodiment 1, except that the mold in this embodiment is a flow field mold, which is a mold with 8 strip grooves protruding toward the inside of the container, the protrusion length, width and height of the strip grooves are 52 mm, 1.2 mm and 1 mm respectively, the length, width and height of the flow field mold are 10 cm, 10 cm and 10 cm respectively, and the structure of the flow field mold is as follows: Figure 2 shown.
[0122] Example 6
[0123] The other conditions of this embodiment are the same as those of embodiment 3, except that the mold for preparing the solidified hydrogel 1 and the reconstituted solidified hydrogel in this embodiment is a flow field mold, which is a mold with 8 strip grooves protruding toward the inside of the container, and the protrusion length, width and height of the strip grooves are 52 mm, 1.2 mm and 1 mm respectively, and the length, width and height of the flow field mold are 10 cm, 10 cm and 10 cm respectively. The structure of the flow field mold is as follows: Figure 2 shown.
[0124] Example 7
[0125] The other conditions of this embodiment are the same as those of embodiment 4, except that the molds for preparing solidified hydrogel 1, solidified hydrogel 2, solidified hydrogel 3 and reconstituted solidified hydrogel in this embodiment are all flow field molds, and the flow field mold is a mold with 8 strip grooves protruding toward the inside of the container, and the protrusion length, width and height of the strip grooves are 52 mm, 1.2 mm and 1 mm respectively, and the length, width and height of the flow field mold are 10 cm, 10 cm and 10 cm respectively. The structure of the flow field mold is as follows: Figure 2 shown.
[0126] Comparative Example 1
[0127] A 6cm*8cm carbon felt (produced by Liaoyang Jingu, with a thickness of 2.4-2.6mm) was activated with water vapor at 500°C for 3h with a heating rate of 30°C / min to obtain a carbon electrode material.
[0128] Test Example 1
[0129] According to Example 6, the thickness gradient nitrogen-doped carbon electrode material prepared in Example 6 has a first gradient, a second gradient and a third gradient, and the thicknesses of the three gradients are the same. The carbon electrode material prepared in Comparative Example 1 can also be equally divided into a first gradient, a second gradient and a third gradient according to thickness.
[0130] The thickness gradient nitrogen-doped carbon electrode material obtained in Example 6 and the carbon electrode material obtained in Comparative Example 1 were cut, and vertical cutting was performed at 1 / 6, 1 / 2 and 5 / 6 along the total thickness direction of the electrode material to obtain 4 samples, namely the first gradient, the one-two mixed gradient, the two-three mixed gradient and the third gradient. The 1 / 6 is located in the middle of the first gradient, the 1 / 2 is located in the middle of the second gradient, and the 5 / 6 is located in the middle of the third gradient. Therefore, the interface at 1 / 6 can reflect the porosity of the first gradient, the interface at 1 / 2 can reflect the porosity of the second gradient, and the interface at 5 / 6 can reflect the porosity of the third gradient. The porosity can be tested in the same cutting direction of the front / back three samples (such as Figure 5 As shown), the three measured data are the porosities of three gradient arrangements (in this test example, the porosities of the first three samples were tested in the same cutting direction).
[0131] The porosity of the first gradient, second gradient and third gradient of the thickness gradient nitrogen-doped carbon electrode material prepared in Example 6 and the carbon electrode material prepared in Comparative Example 1 were tested using a mercury porosimeter (produced by PMI, USA). The test results are shown in Table 1.
[0132] Table 1: Porosity of the first gradient, second gradient and third gradient of the thickness gradient nitrogen-doped carbon electrode material prepared in Example 6 and the carbon electrode material prepared in Comparative Example 1
[0133]
[0134] The results show that compared with Comparative Example 1, the porosity of the three samples in Example 6 presents a gradient change.
[0135] Test Example 2
[0136] The nitrogen-doped carbon electrode materials prepared in Examples 1-7 and the carbon electrode material prepared in Comparative Example 1 were assembled into a flow battery and the battery characteristics (energy efficiency and voltage efficiency) were tested.
[0137] Cutting method of electrode material: The size of the electrode is 6cm×8cm. When setting the gradient between the inlet and outlet, it is necessary to ensure that the electrode is cut in the center so that the range on the left and right sides is consistent. When it comes to the flow channel, it is necessary to ensure that the flow channel direction is perpendicular to the long direction of the electrode; therefore, when sampling the electrode material (especially the electrode material of Examples 4-7), the sample should be taken in the center to ensure that multiple concentration gradients are obtained and the flow channel direction is correct. For specific cutting methods, refer to Figure 3 .
[0138] Preparation conditions of liquid flow battery: The active substances in the positive and negative electrolytes are 1.7 mol / LV respectively 4+ / V 5+ and 1.7 mol / LV 2+ / V 3+ The supporting electrolyte is 4 mol / L sulfuric acid. The volume of the positive and negative electrolytes is 70 mL. The perfluorosulfonic acid proton membrane is produced by Suzhou Kerun. The effective area of the electrode is 48 cm 2 , flat graphite plate, compression ratio is 20%.
[0139] Battery characteristic test: constant current test, the electric density is 80, 110, 160, 200mA / cm 2 The upper limit of charge is 1.55V, the lower limit of discharge is 1.00V, and the cycle is repeated 5 times at each current density. The data of the 4th cycle is taken as the result for each current density. The test results are shown in Table 2.
[0140] Table 2: Energy efficiency and voltage efficiency of flow batteries assembled from nitrogen-doped carbon electrode materials prepared in Examples 1-7 and carbon electrode materials prepared in Comparative Example 1
[0141]
Claims
1. A method for preparing a nitrogen-doped carbon electrode material, characterized in that: The method comprises the following steps: (1) dissolving an amine-containing hydrophilic polymer in water to obtain a first hydrogel precursor solution; dissolving an aldehyde-containing hydrophilic polymer in water to obtain a second hydrogel precursor solution; mixing the first hydrogel precursor solution and the second hydrogel precursor solution evenly, pouring the mixture into a mold, sealing the mold and allowing the mold to stand to obtain a solidified hydrogel; (2) pre-freezing the solidified hydrogel and then freeze-drying it to obtain a freeze-dried hydrogel with a self-supporting structure; (3) The freeze-dried hydrogel is carbonized and activated to obtain a nitrogen-doped carbon electrode material.
2. The method according to claim 1, characterized in that The method has one or more of the following features: In step (1), the amino-containing hydrophilic polymer is selected from one or more of chitosan, carboxymethyl chitosan, polyethyleneimine and gelatin; In step (1), the concentration of the amino-containing hydrophilic polymer in the first hydrogel precursor solution is 0.5 to 2 mol / L; In step (1), the aldehyde-containing hydrophilic polymer is selected from one or more of oxidized alginate, oxidized hyaluronic acid and polyacrylaldehyde; In step (1), the concentration of the hydrophilic polymer containing aldehyde groups in the second hydrogel precursor solution is 0.5 to 2 mol / L; In step (1), the first hydrogel precursor solution and the second hydrogel precursor solution are mixed in a volume ratio of (1-3):1; In step (1), the mold is a common mold with a flat and smooth bottom or a flow field mold with a convex or concave structure on the bottom; In step (1), the standing time is 0.5 to 6 hours; In step (2), the pre-freezing temperature is -15 to -5°C; In step (2), the pre-freezing time is 8 to 24 hours; In step (2), the freeze-drying temperature is -50 to -40°C; In step (2), the vacuum degree of freeze drying is 10-20 Pa; In step (2), the freeze-drying time is 24 to 72 hours; In step (3), the temperature of the carbonization treatment is 600-700° C.; In step (3), the heating rate of the carbonization treatment is 10 to 50°C / min; In step (3), the heat preservation time of the carbonization treatment is 2 to 5 hours; In step (3), carbonization is carried out in an inert gas or nitrogen atmosphere; In step (3), steam activation or air activation is used; In step (3), the temperature of the activation treatment is 300-600°C; In step (3), the heating rate of the activation treatment is 10 to 50°C / min; In step (3), the holding time of the activation treatment is 2 to 5 hours.
3. The method according to claim 1, characterized in that The method further comprises step (1'): preparing solidified hydrogels of different concentrations according to the operation of step (1), cutting the solidified hydrogels of different concentrations to obtain solidified hydrogel strips of different concentrations, laminating the solidified hydrogel strips of different concentrations along the cut surface, placing them in a mold, sealing and standing them to obtain reconstituted solidified hydrogels, and then performing the operations of steps (2) and (3) on the reconstituted solidified hydrogels.
4. The method according to claim 3, characterized in that The method has one or more of the following features: In step (1'), the cutting method is horizontal cutting or vertical cutting; In step (1'), the bonded solidified hydrogel strip is placed in the mold in a manner that the cut surface is parallel or perpendicular to the bottom of the mold; In step (1'), the mold is a common mold with a flat and smooth bottom or a flow field mold with a convex or concave structure on the bottom; In step (1'), the standing time is 3 to 6 hours; The molds used in step (1) and step (1') may be the same or different.
5. A nitrogen-doped carbon electrode material, characterized in that: The nitrogen-doped carbon electrode material is prepared by the method according to any one of claims 1 to 4, and the nitrogen-doped carbon electrode material is a single-layer nitrogen-doped carbon electrode material or a gradient nitrogen-doped carbon electrode material.
6. The nitrogen-doped carbon electrode material according to claim 5, characterized in that The nitrogen-doped carbon electrode material has a flow field.
7. The nitrogen-doped carbon electrode material according to claim 5, characterized in that The porosity of the gradient nitrogen-doped carbon electrode material changes in a gradient; and / or The gradient number of the gradient nitrogen-doped carbon electrode material is ≥1.
8. The nitrogen-doped carbon electrode material according to claim 5, characterized in that: The gradient nitrogen-doped carbon electrode material includes a thickness gradient nitrogen-doped carbon electrode material or a vertical gradient nitrogen-doped carbon electrode material.
9. The nitrogen-doped carbon electrode material according to claim 8, characterized in that The porosity of the thickness gradient nitrogen-doped carbon electrode material changes gradiently in the thickness direction, and the porosity of the vertical gradient nitrogen-doped carbon electrode material changes gradiently in the direction perpendicular to the thickness direction.
10. A liquid flow battery, characterized in that: The liquid flow battery comprises the nitrogen-doped carbon electrode material according to any one of claims 5-9.